PERHITUNGAN RUANG TERBUKA HIJAU PERKOTAAN JENIS PUBLIK (STUDI KASUS : KOTA SURAKARTA) - Wahyuningsih,, Hapsari (Universitas Aisyiyah Yogyakarta, 2018)
Abstract: This research was conducted on 4 aspects, namely: (1) Aspect of Urban Green Open Space, (2) Aspect of Urban Land Use, (3) Aspect of Urban Land Utilization, and (4) Aspect of Public Green Open Space. Research methods are using Geographic Information System (GIS), research framework adopt from Peraturan Menteri PU no 12 / PRT / M / 2009 (Pedoman Penyediaan dan Pemanfaatan Ruang Terbuka Non Hijau Di Wilayah Kota/Kawasan Perkotaan ) and Peraturan Menteri PU no 05/PRT/M/2008 ( Pedoman Penyediaan dan Pemanfaatan Ruang Terbuka Hijau di Wilayah Kota/Kawasan Perkotaan). Result of research that (1) understanding of public green open space, (2)The occurrence of change of public green open space and (3) the existing area of Public green open space of Surakarta City to the total city area as a whole.